The Influence of Inventory Management and Quality Management on Sales at PT Coca Cola Europacific Partners - Alvia Rahmah; Nuri Aslami; Nurbaiti Nurbaiti (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
This study aims to analyze the influence of inventory management and quality management on sales at PT Coca-Cola Europacific Partners in Medan City. In the competitive soft drink industry, maintaining business performance requires efficient inventory management and strict quality control. By using documents, interviews, and questionnaires based on the Slovin formula, this study collected data from 60 respondents. A quantitative research approach was applied through multiple linear regression analysis techniques which were utilized as data processing tools. The results reflect that quality management and inventory management both increase sales partially and significantly. The R² value obtained of 0.932 indicates that the two independent variables are able to explain 93.2% of the variation in sales. Thus, the integration of inventory and quality strategies plays an important role in increasing sales volume and effectiveness.